Sodium pyrophosphate enhances iron bioavailability from bouillon cubes fortified with ferric pyrophosphate. Issue 3 (8th June 2016) - Cercamondi, Colin I.; Duchateau, Guus S. M. J. E.; Harika, Rajwinder K.; van den Berg, Robin; Murray, Peter; Koppenol, Wieneke P.; Zeder, Christophe; Zimmermann, Michael B.; Moretti, Diego
Abstract: Fe fortification of centrally manufactured and frequently consumed condiments such as bouillon cubes could help prevent Fe deficiency in developing countries. However, Fe compounds that do not cause sensory changes in the fortified product, such as ferric pyrophosphate (FePP), exhibit low absorption in humans. Tetra sodium pyrophosphate (NaPP) can form soluble complexes with Fe, which could increase Fe bioavailability. Therefore, the aim of this study was to investigate Fe bioavailability from bouillon cubes fortified with either FePP only, FePP+NaPP, ferrous sulphate (FeSO4 ) only, or FeSO4 +NaPP. We first conducted in vitro studies using a protocol of simulated digestion to assess the dialysable and ionic Fe, and the cellular ferritin response in a Caco-2 cell model. Second, Fe absorption from bouillon prepared from intrinsically labelled cubes (2·5 mg stable Fe isotopes/cube) was assessed in twenty-four Fe-deficient women, by measuring Fe incorporation into erythrocytes 2 weeks after consumption. Fe bioavailability in humans increased by 46 % ( P <0·005) when comparing bouillons fortified with FePP only (4·4 %) and bouillons fortified with FePP+NaPP (6·4 %). Fe absorption from bouillons fortified with FeSO4 only and with FeSO4 +NaPP was 33·8 and 27·8 %, respectively (NS). The outcome from the human study is in agreement with the dialysable Fe from the in vitro experiments. Our findings suggest that the addition of NaPP could be a promising strategy to increase Fe absorption from FePP-fortified bouillon cubes, and if confirmed by further research, for other fortified foods with complex food matrices as well.